Synergistic cooling effects of UV protective shading and PV-ESS powered ventilation on pedestrian-level microclimate and modelled physiological heat stress - Shisheng Chen; Weiwei Yang; Jiayan Fu; Zhongqi Yu; Yumeng Jin; Meng Zhen; Lei Xu; Ruohan Xu; Chao Cen (Building and Environment, 2026)

Global Patterns and Drivers of Recent Decoupling Between Extratropical Spring Phenology and Temperature - Ziyu Lu; Ming Shao; Jiayan Li; Jingyuan Lin; Peiyuan Tao; Mengyu Li; Siqi Zhang; Peng Yao; Yang Fu (Global Change Biology, 2026)
While spring phenology has been widely studied, the magnitude and drivers of its decoupling from thermal cues across extratropical biomes remain poorly understood. Using satellite data from 1982 to 2021, we show that the onset of vegetation green‐up (GSOS) generally lags the onset of the thermal growing season (TSOS). This mismatch (ΔSOS) has increased by 1.51 days per decade ( p 15 days), warming‐driven advances in TSOS are increasingly decoupled from GSOS, as declining precipitation and enhanced evaporative demand intensify moisture limitation and delay green‐up; in temperate forests (both coniferous and broadleaf), warming together with enhanced shortwave radiation promotes faster GSOS advancement relative to TSOS, thereby dampening the mismatch. These contrasting pathways reveal an accelerating yet heterogeneous phenology–temperature decoupling, with far‐reaching consequences for ecosystem synchrony, seasonal carbon uptake, and land–climate feedbacks. Our results underscore the need to incorporate non‐thermal drivers and biome‐specific controls into phenological and Earth system models to better constrain future climate–biosphere interactions.

Quantifying key design factors for thermal comfort in underground space through global sensitivity analysis and machine learning - Shisheng Chen; Nyuk Hien Wong; Chao Cen; Ruohan Xu; Lei Xu; Zhenjiang Shen; Zhigang Wu; Jiayan Fu; Zhongqi Yu (Tunnelling and Underground Space Technology, 2026)

A single Drosophila Dscam1 genomic locus generates a vast repertoire of circRNAs facilitated by RNA pairing - Zedong Li; Bingbing Xu; Zhechao Wang; Wenjie Zhang; Jiayan Fu; Lili Wu; Nengcheng Bao; Jinpeng Xie; Ru Yan; Haiyang Dong; Yongfeng Jin (Insect Biochemistry and Molecular Biology, 2025)

Biomimetic spinning of glassy ionogel fibers with tailorable mechanical properties for versatile applications - Tian Zhang; Leang Yin; Zengyu Hui; Runrun Zhang; Jiayan Fu; Hai Xu; Jingbo Zhou; Wenteng Hou; Yi Yao; Jianing An; Hongqing Pan; Gengzhi Sun (Chemical Engineering Journal, 2025)

Analysis of intrinsic effects of compound curing agents on small molecule metabolites and microbial communities in Xuanwei ham based on metabolomics and high-throughput sequencing - Zhijie Zheng; Wenxi Fu; Guiying Wang; Bo Li; Wen Xun; Nannan Zhou; Chunfang Yang; Ruwei Ren; Shuai Tang; Yanfei Du; Jiayan Tan; Dahai Gu; et al. (Meat Science, 2025)

Tabular prior-data fitted network for urban air temperature inference and high temperature risk assessment - Zhongqi Yu; Ruqing Yu; Xinyi Ge; Jiayan Fu; Yiteng Hu; Shisheng Chen (Sustainable Cities and Society, 2025)

Inter-individual variation in human microbiota drives differential impacts on the fermentability of insoluble bran by soluble β-glucans from whole barley - Songtao Fan; Yiwei Ding; Zikang Hu; Zhihong Zhang; Lin Fu; Jiayan Zhang; Ying Zhu; Juan Bai; Xiang Xiao (Food Hydrocolloids, 2025)

Enhancing performance and generalization in dormitory optimization using deep reinforcement learning with embedded surrogate model - Zewei Shi; Chenyu Huang; Jinyu Wang; Zhongqi Yu; Jiayan Fu; Jiawei Yao (Building and Environment, 2025)

Simultaneous monitoring of creatinine and urea in diversified clinical samples based on SERS-active PDMS-flower-like ZIF-67@Ag nanoparticles - Mijia Liu; Shijiao Fu; Jiayan Xu; Chenyi Yuan; Jianwei Ma; Chenjie Gu; Tao Jiang; Xueyan Bian (Analytica Chimica Acta, 2025)

Efficient data-driven prediction of household carbon footprint in China with limited features - Na An; Chenyu Huang; Yanting Shen; Jinyu Wang; Zhongqi Yu; Jiayan Fu; Xiao Liu; Jiawei Yao (Energy Policy, 2024)

Exploring spatial and environmental heterogeneity affecting energy consumption in commercial buildings using machine learning - Yijun Lu; Qiyue Chen; Mengqing Yu; Zihao Wu; Chenyu Huang; Jiayan Fu; Zhongqi Yu; Jiawei Yao (Sustainable Cities and Society, 2023)

Physiological functions of urea transporter B - Lanying Yu; Tiantian Liu; Shuang Fu; Li Li; Xiaoping Meng; Xin Su; Zhanfeng Xie; Jiayan Ren; Yan Meng; Xuejiao Lv; Yanwei Du (Pflügers Archiv - European Journal of Physiology, 2019)
Urea transporters (UTs) are membrane proteins in the urea transporter protein A (UT-A) and urea transporter protein B (UT-B) families. UT-B is mainly expressed in endothelial cell membrane of the renal medulla and in other tissues, including the brain, heart, pancreas, colon, bladder, bone marrow, and cochlea. UT-B is responsible for the maintenance of urea concentration, male reproductive function, blood pressure, bone metabolism, and brain astrocyte and cardiac functions. Its deficiency and dysfunction contribute to the pathogenesis of many diseases. Actually, UT-B deficiency increases the sensitivity of bladder epithelial cells to apoptosis triggers in mice and UT-B-null mice develop II-III atrioventricular block and depression. The expression of UT-B in the rumen of cow and sheep may participate in digestive function. However, there is no systemic review to discuss the UT-B functions. Here, we update research approaches to understanding the functions of UT-B.

Rice OsPEX1, an extensin-like protein, affects lignin biosynthesis and plant growth - Shanwen Ke; Xin Luan; Jiayan Liang; Yu-Hung Hung; Tzung-Fu Hsieh; Xiang-Qian Zhang (Plant Molecular Biology, 2019)